De Eventu Futurorum. Translation into Lithuanian and commentaries: Živilė Pabijutaitė - Lavenhamas, Ričardas (Problemos, 2018)
[text in Lithuanian]Foreword, translation into Lithuanian and commentaries: Živilė PabijutaitėTranslated from: Richardus Lavenhamus, 1983. De eventu futurorum. In: Richard Lavenham on Future Contingents, ed. by Øhrstrøm P. Cahiers de l‘Institut du Moyen-Age, , 180–186
Keywords: none